Site-specific gene knock-in and bacterial phytase gene expression in Chlamydomonas reinhardtii via Cas9 RNP-mediated HDR - Zadabbas Shahabadi, Hassan; Akbarzadeh, Arash; Ofoghi, Hamideh; Kadkhodaei, Saeid (Frontiers in Plant Science, 2023)
In the present study, we applied the HDR (homology-directed DNA repair) CRISPR-Cas9-mediated knock-in system to accurately insert an optimized foreign bacterial Phytase gene at a specific site of nitrate reductase (NR) gene (exon 2) to achieve homologous recombination with the stability of the transgene and reduce insertion site effects or gene silencing. To this end, we have successfully knocked-in the targeted NR gene of Chlamydomonas reinhardtii using the bacterial phytase gene cassette through direct delivery of CRISPR/Cas9 system as the ribonucleoprotein (RNP) complex consisting of Cas9 protein and the specific single guide RNAs (sgRNA). The NR insertion site editing was confirmed by PCR and sequencing of the transgene positive clones. Moreover, 24 clones with correct editing were obtained, where the phytase gene cassette was located in exon 2 of the NR gene, and the editing efficiency was determined 14.81%. Additionally, site-specific gene expression was analyzed and confirmed using RT-qPCR. Cultivation of the positive knocked-in colonies on the selective media during 10 generations indicated the stability of the correct editing without gene silencing or negative insertion site effects. Our results demonstrated that CRISPR-Cas9-mediated knock-in could be applied for nuclear expression of the heterologous gene of interest, and also confirmed its efficacy as an effective tool to site-specific gene knock-in, avoiding nuclear positional effects and gene silencing in C. reinhardtii. These findings could also provide a new perspective on the advantageous application of RNP-CRISPR/Cas9 gene-editing to accelerate commercial production of complex recombinant proteins in the food-grade organism "C. reinhardtii".